Inspirational leadership and work environment during the pandemic in Peruvian workers - Dávila-Morán, Roberto Carlos (2024)
The purpose of this paper is to examine how charismatic leadership and work environment are related during the pandemic in workers in Peru. The research is of a quantitative and correlational, non-experimental nature, of a basic nature; in which 423 workers from five companies from various sectors located in Lima, Callao and Trujillo, in Peru, participated. Two Likert scale questionnaires were used, each consisting of 20 statements and 5 response options. It was found that 62.51% report charismatic leadership at a regular level, while the work environment is perceived by 62.08% in a regular category. Deriving that, there is evidence to argue that charismatic leadership is related in a statistically significant way with the work environment, that is, as the level of charismatic leadership increases, the level of work environment in workers also increases.